Exploring the thermal limit of GaN power devices under extreme overload conditions. (September 2017) - Pribahsnik, F.P.; Nelhiebel, M.; Mataln, M.; Bernardoni, M.; Prechtl, G.; Altmann, F.; Poppitz, D.; Lindemann, A.
Abstract: The performance of normally-off Gallium-Nitride (GaN) High-Electron-Mobility-Transistors (HEMTs) under extended short circuit operation is investigated. A thermal limit is found in the aluminium metallization, where at temperatures around 600 °C a protrusion of the gate metal through the Inter-Level Dielectric (ILD) may form, short-circuiting gate and source metallization and thus resulting in a permanently-off failure state. The present work shows how this particular failure mode can be induced by extreme overload operation, and presents a Finite Element (FE) model which agrees with the experimental observations and gives insights in the mechanical stress-state developing in the device. The deeper thermo-mechanical understanding of the degradation mechanism suggests directions in order to improve the device's robustness. Highlights: Novel failure mode in power GaN devices has been studied Failure mode explained by thermal-transient and thermo-mechanical FEM simulation Failure mode root cause is an overstress located in the interlayer dielectric